Enhanced cancer cell sorting using lab-on-a-disk pattern design with magnetic and centrifugal forces - Cheng, Bill; Chao, Wei-Cheng; Chen, Yi-Han; Lin, Yao-Tsung (Frontiers in Bioengineering and Biotechnology, 2025)
Using microfluidic flow for biological detection is a non-invasive method that can replace traditional invasive testing methods to achieve fast and accurate results. The design of the detection device and lab-on-a-disk (LoaD) can impact performance in accurately identifying biological features. Therefore, we created a novel device to extract cancer cells from a heterogeneous cell population by centrifugal-force-driven microfluidic flow and magnetic labeling. Two-stage centrifugal force and a specially designed LoaD were used to drive microfluidic flow and control its movement to designated areas. The purpose was to allow the CD44 antibody–magnetic bead complex (CD44 beads), which specifically binds to the abundantly present CD44 receptors on identifiable cancer cells, to flow into the reservoir well, while the biological mixture containing the cancer cells is retained in the capture well. Fluorescence imaging as well as flow cytometric analysis revealed the successful retention of the microbead-bound cancer cells in the magnetic area, while the remaining biological mixture was retained in the reservoir area. The entire separation process took less than 2 h.